E-Health ICOnnecta’t program: An ecosystem to promote wellbing in cancer towards ONCOMMUN European proposal - Ochoa-Arnedo, Cristian; Flix-Valle, Aida; Medina, Joan Carles; Escriche, Elisenda; Rodríguez, Ana; Villanueva, Claudia; Sumalla, Enric C.; Alabèrnia-Segura, Miquel; Prats, Claudia; Corral, María José; Gallardo-Pujol, David; Feixas, Guillem; et al. (Psicooncología, 2020)
Introduction: Although psycho-oncological treatments have already demonstrated their effectiveness in reducing emotional distress and improving quality of life in people with cancer, there are still numerous barriers limiting their access. The digital transformation of care is proposed as a solution to increase service coverage and improve its cost-utility. Aim: Create a digital health ecosystem to reduce the impact of cancer, increasing users’ well-being and quality of life. Method: The program is addressed to patients diagnosed with breast cancer in the acute survival phase. It is a stepped-care intervention divided into 4 levels ordered by complexity: Level 1, psychosocial screening and monitoring; Level 2, Campus: psychoeducation and health education; Level 3, psychosocial community support; and Level 4, psychotherapeutic group treatment. Results: In 2019, 259 women were included in the program (39.91% of new breast cancer cases in participating centers), and only 3.47% (n = 9) required specialized clinical care (Level 4). Conclusions: The Iconnecta’t program adopts an integrated model of psychosocial care in cancer that adapts to survivors’ specific needs. It overcomes some of the barriers of traditional healthcare, democratizing service access through the use of common technologies among the vast majority of citizens. In the near future, progressive implementation to other cancer diagnoses is planned, together with a randomized controlled trial to evaluate its effectiveness.
Keywords: E-Health; comprehensive attention; Internet prescription; breast cancer; psycho-oncology; health psychology